Selective Immunoglobulin M Deficiency in Patients with Autoimmune Liver Diseases - H. Balaban, Yasemin; Ismail, Mohamed; Nur Ayar, Şefika (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Balaban YH, Ismail M, Nur Ayar Ş. Selective immunoglobulin M deficiency in patients with autoimmune liver diseases. Turk J Gastroenterol. 2024;35(6):505-508.